mir-276a Is Required for Muscle Development in Drosophila and Regulates the FGF Receptor Heartless During the Migration of Nascent Myotubes in the Testis - Mathieu Preußner; Maik Bischoff; Susanne Filiz Önel (Cells)
MicroRNAs function as post-transcriptional regulators in gene expression and control a broad range of biological processes in metazoans. The formation of multinucleated muscles is essential for locomotion, growth, and muscle repair. microRNAs have also emerged as important regulators for muscle development and function. In order to identify new microRNAs required for muscle formation, we have performed a large microRNA overexpression screen. We screened for defects during embryonic and adult muscle formation. Here, we describe the identification of mir-276a as a regulator for muscle migration during testis formation. The mir-276a overexpression phenotype in testis muscles resembles the loss-of-function phenotype of heartless. A GFP sensor assay reveals that the 3′UTR of heartless is a target of mir-276a. Furthermore, we found that mir-276a is essential for the proper development of indirect flight muscles and describe a method for determining the number of nuclei for each of the six longitudinal muscle fibers (DLMs), which are part of the indirect flight muscles.